Marketing Politik Partai Gerindra Untuk Pemenangan Pemilu Legislatif Kabupaten Kebumen Tahun 2019 - Ganis - Wisnujati; Fitriyah - -; Yuwanto - - (Journal of Politic and Government Studies, 2021)
The results of the 2019 Simultaneous Elections placed the Gerindra Party in the top three positions for the most seats in the Kebumen Regency Legislative Election in 2019. Among the parties that carried Prabowo-Sandi, only the Gerindra Party was able to maintain the Regional House of Representatives seats. On the other hand, positive achievements of the Gerindra Party in the political arena in Kebumen Regency also cannot be negated. Therefore, this study aims to explain and analyze the strategy of the Gerindra Party, especially in winning the 2019 Legislative Election. This study uses a qualitative method with a case study approach that applies data collection techniques through interviews with resource persons and documentation studies. The data obtained were then analyzed using the 4P political marketing theory and the coattail effect theory. The results showed that in their success in maintaining the number of Regional House of Representatives seats, the Gerindra Party and legislative candidates applied the principles of political marketing. Networks owned by candidates and parties are very influential in winning elections. On the other hand, there are efforts by the Gerindra Party and legislative candidates in marketing the figures of the presidential and vice presidential candidates. So that Prabowo-Sandi is increasingly known to the public and legislative candidates get the impact of the coattail effect.